AIDS-Related Extrapulmonary Pneumocystis carinii Infection Presenting as a Solitary Rectal Ulcer - Eric M Yoshida; Douglas Filipenko; Peter Phillips; Julio SG Montaner; J Scott Whittaker (Canadian Journal of Gastroenterology)
Extrapulmonary infection with Pneumocystis carinii, although uncommon, is increasingly recognized. Use of aerosolized pentamidine versus a systemic medication is thought to be a contributing factor due to the low concentrations of drug that are incapable of suppressing systemic infection. Infection with P carinii has been reported in every organ system including the gastrointestinal system. A 28-year-old acquired immunodeficiency syndrome patient receiving prophylaxis with aerosolized pentamidine who presented with a solitary rectal ulcer is reported. Initial biopsy was characteristic of extrapulmonary P carinii infection, with numerous organisms present. Occasional cytomegalovirus inclusion bodies were noted which may have been a copathogen but which were not treated. Treatment with intravenous pentamidine resulted in documented eradication of P carinii and complete resolution of the ulcer. Although lower gastrointestinal pneumocystosis has been described without ulceration, this is the first description of rectal ulceration presenting as the initial manifestation of extrapulmonary pneumocystosis.